Analisis Kondisi Bisnis BMT Bahtera Dalam Memasuki Pasar Industri Jasa Keuangan Syariah : Pendekatan General Electric - Ani Rohanah; Azahra, Dian Fatimah; Sendy, Debby Laura; Shafrani, Yoiz Shofwa (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the business condition of BMT Bahtera in entering the market of the syariah financial services industry using a General Electric Matrix approach. The method used in this study was in-depth interviews with the internal informant from BMT. The research result shows that BMT Bahtera’s strength is on the digitalization services, Human Resources competencies and saving and financing products innovation. Despite recently entering the Purwokerto territory, the business is growing with high potential market share using direct promotion strategy and effective institutional cooperation.